Hubungan Psikologi Perkembangan Anak Didik Tehadap Efektivitas Pembelajaran Pendidikan Agama Islam Siswa Kelas X SMK Swasta Gebang - Ahmad Sanusi Lukman, Muamar Al Qadri, Nurliza Afni (Pusdikra-Publishing.com, 2022)
Based on the results of the data description, analysis requirements test, research results, research findings and research limitations, the researchers concluded that the developmental psychology of students who had an average result of 51.7 median was 55.3 mode was 53.8 the variance was 28.75 and standard deviation of 5.36 is acceptable with a significant tolerance limit. This indicates a positive and significant relationship. The effectiveness of Islamic religious education at Gebang Private Vocational School has an average result of 53.4 median of 54.1 mode of 53.3 variance of 18.73 and standard deviation of 4.33 acceptable with a significant tolerance limit. This indicates a positive and significant relationship. There is a positive and significant relationship in the psychology of the development of students with the effectiveness of Islamic religious education at the Gebang Private Vocational School with a regression line Y=22.10 +0.61 X. There is a significant correlation between the psychology of the development of students and the effectiveness of Islamic religious education in SMK Private Gebang, Gebang District, after doing a regression test with the product moment formula with a calculated result of 0.837 with a strong or high level of relationship.